Social-emotional Education in Local Heritage: Patrimonial Activities Outside the Classroom - Fuentes Moncada, Leonel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Social-emotional learning is a tendency in education and must be accounted for in all areas of study. Heritage education cannot ignore this reality and must include and its planning and delivery effective strategies to implement and promote social-emotional competencies. The following work, proves patrimonial visits are an innovative approach towards coping with emotions in society. The activity proposed and studied in this investigation demonstrated the opportunities for integer learning during these experiences are real and cause a significant impact in students and society. This study demonstrated the most relevant aspects to consider in patrimonial visits.